Effect of COVID-19 vaccination coverage on transmission and mortality during Omicron dominance - Stephen Chukwuma Ogbodo; Joseph Junior Damba; Omotayo Olaoye; Divine-Favour Chichenim Ofili; Adaeze Augustina Ngwu (Academia Medicine)
Background: During the coronavirus disease 2019 (COVID-19) pandemic, the emergence of the Omicron SARS-CoV2 variant raised concerns about reduction in vaccine effectiveness due to its higher transmissibility. Thus, using ecologic data, we assessed the population-level impact of COVID-19 vaccination coverage on COVID-19 transmission and mortality, during the period of Omicron dominance globally. Subject and methods: We used a longitudinal dataset of 110 countries over 16 months (January 2022 to April 2023). Applying random-effects regression models, we assessed the effect of monthly full vaccination coverage on the rates of newly confirmed COVID-19 cases and deaths, adjusting for country characteristics. We obtained the data from open-access databases, including the World Health Organization (WHO) COVID-19 Dashboard and the Oxford COVID-19 Government Response Tracker. Results: On average, each 1% point increase in full vaccination coverage was associated with a 1.4% reduction (95% confidence interval (CI): 0.1%–2.8%, p = 0.035) in the rate of new cases and a 5% reduction (95% CI: 3.6%–6.4%, p < 0.001) in the rate of deaths. This protective effect of vaccination was graded across the levels of vaccination coverage: compared to countries with <50% vaccination coverage, those with coverages of 50%–59%, 60%–69%, 70%–79%, and ≥80% had 20.5% (95% CI: –16.4%–45.7%), 53.8% (22.6%–72.5%), 54.3% (15.5%–75.3%), and 69.6% (38.7%–84.9%) lower rates of new cases, respectively, on average. Conclusions: Our findings suggest an important role of vaccination in mitigating the impact of pandemics, particularly despite the emergence of highly transmissible variants like Omicron.